Запозичення як одна із причин мовної синонімії: культурологічний аспект - Руснак, Наталія Олександрівна; Струк, Іванна Михайлівна (Ужгород: Видавничий дім «Гельветика», 2022)
One of the features of the lexical system of the Ukrainian language is a widely developed synonymy. The article analyzes lexical borrowings, which are one of the reasons for linguistic synonymy in the modern Ukrainian language. Broad and narrow understanding of the term „borrowing” is taken into account. A broad understanding made it possible to find out the origin of names and the path of their semantic and structural development, a narrow one – to take into account the intermediary languages – through which the word entered the Ukrainian language. The analysis was carried out taking into account the cultural aspect of the study of borrowed names, with the involvement of cultural information, based on the Etymological Dictionary of the Ukrainian Language, the Dictionary of Foreign Words, the Dictionary of Bukovinian idioms, explanatory dictionaries. Absolute lexical synonyms that appeared as a result of borrowings from different languages – to designate one denotation are considered (янтар, бурштин). Attention is drawn to doublet words in Bukovinian dialects, which differ in their origin (абрикос, дзендзури, муралі). Synonymous series and synonymous pairs are presented which are represented by actually Ukrainian and borrowed lexemes. It was found that the phenomenon of absolute synonymy often arises as a result of word-forming traces which are characterized by one internal form (описовий – дескриптивний). The internal form of a foreign word within a word combination often duplicates the internal form of a Ukrainian word which is the cause of stylistic errors (прейскурант цін). The use of borrowed names in the Ukrainian language motivates such a linguistic phenomenon as purism. Two coerses of purism are noted in Ukrainian linguistic thought – extreme and moderate. This phenomenon is illustrated in S. Karavanskyi's work „Secrets of the Ukrainian Language”. The continuation of S. Karavanskyi's ideas is Ukrainian journalist, musicologist, publicist, public figure Yurko Zeleny, who believes that currently the biggest problem of the Ukrainian language is anglicism. Purist tendencies are characteristic of modern mass media (водограй instead of фонтан, гвинтокрил – вертоліт, славень – гімн).
Borrowing as one of the causes of language synonymy: a cultural aspect
Keywords: borrowing; lexical synonymy; doublet words; literal translation; internal form; purism